Dielectric properties of alumina doped with TiO2 from 13 to 73 GHz. Issue 2 (February 2017) - Marco, D. Di; Drissi, K.; Geffroy, P.-M.; Delhote, N.; Tantot, O.; Verdeyme, S.; Chartier, T.
Abstract: Recent studies show that alumina doped with TiO2 exhibits promising dielectric properties, corresponding to low loss tangents and low temperature coefficients (or close to 0 ppmC −1 ). This paper aims to confirm these trends and study the dielectric properties of alumina doped with TiO2 from 0.5% to 12% wt. at high frequency, 13–73 GHz. This work demonstrates that alumina doped with TiO2 corresponds to potential materials for frequency converter devices working at a high frequency (up to 50 GHz).